Cooperation, trust, security? The potential and limits of the OSCE's economic and environmental dimension - Franziska Smolnik (Stiftung Wissenschaft und Politik (SWP), 2019)
In the context of a European security order under pressure, the OSCE - and its long neglected economic and environmental dimension - has developed a new dynamism. The potential for generating trust in this area is attributed to the idea that economics and the environment are supposedly less sensitive issues to cooperate on. The assumption is that this trust can subsequently have a positive effect on cooperation in other fields, and contribute to greater security in Europe as a whole. In this regard, the results of this study suggest that we should manage expectations pragmatically: the chances of cooperation on OSCE "second-dimension" issues should be kept in perspective. A greater degree of intergovernmental cooperation does not automatically mean an increase in trust, nor does spillover between "low politics" and "high politics" necessarily occur. Alongside its EU partners, Germany should therefore pay particular attention as to how to upgrade the OSCE's economic and environmental dimension. Connections between the OSCE dimensions should be actively promoted; debates in the "second dimension" could be even more closely tied to the discussion on the crumbling basic consensus over rule-based order and common principles.
Keywords: 320